Analisis Pendapatan dan Tingkat Kemiskinan Rumah Tangga Petani Padi di Kecamatan Tambelang Kabupaten Bekasi - Zakiyah Stianing Islamiant; Abu Bakar; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2023)
The income level of farmers in general can be influenced by several aspects, namely the area of ​​land, the amount of production, the selling price, and the production costs of farming. Apart from farming, farmers usually seek income from outside the farm. According to Soekartawi (2003), the level of farm income, apart from being the main determinant of the welfare of farmer households, also appears as one of the important factors that condition economic growth. Poverty is closely related to welfare, reflected in the fulfillment of basic needs and increased purchasing power. Tambelang sub-district, the average population who works as farmers has income outside of farming. Due to suffice for the welfare of the farmer's household itself. The aims of this study were: to determine farm income, farmer household income, and the poverty rate of rice farming households in Tambelang District, Bekasi Regency. The results showed that the average farming income per farmer planting season was Rp 9,208,890 and for farming income per month was Rp 2,302,222 in one month. The average income of farmer households in one planting season is Rp 27,111,339/ha and for a month it is Rp 6,777,834/ha. Based on the criteria of the Sajogyo method, the criteria for "a decent household life" from farming income are 32 respondents and household income are 40 respondents.